PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATA PELAJARAN PENDIDIKAN PANCASILA PESERTA DIDIK KELAS III SD - Kusworo, Alivia Cahya; Pangestu, Deviyanti; Rizqi, Yoga Fernando; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the lack of critical thinking skills among third-grade students at SDN 6 Metro Barat. The purpose of this study is to determine the effect of implementing the Problem-Based Learning (PBL) model on critical thinking skills in the Pancasila Education subject. This study employed a quasi-experimental design with a nonequivalent control group design. The population consisted of 76 students, and the sample comprised 50 third-grade students 24 from Class III A and 26 from Class III B at SDN 6 Metro Barat. The sampling technique used was non-probability sampling via purposive sampling. Data analysis was conducted using simple linear regression. The simple linear regression test indicated a significant effect of the Problem-Based Learning (PBL) model on critical thinking skills in the Pancasila Education subject, with a contribution of 60%. The PBL model was proven to be effective in improving the critical thinking skills of third-grade students at SDN 6 Metro Barat in the Pancasila Education subject.